An Analysis of the Single Window System in Taiwan - Hsin-I, Wen (2009)
Nowadays, what supply chains tend to achieve are to minimise costs and to create value and tend to collaborate and share information in order to make operations more efficient and responsive. However, non-visible barriers still impacts the performance logistics as being across national borders. Complicated procedures and regulatory requirements at the borders usually lead to lots of transaction costs and might unexpected delay of goods flow. impact the performance of global supply chain. The implementation of single window aims to strengthen the information flow between governments and traders in order to speed the goods clearance as well as well communication in order to minimise uncertainty in border operations. Taiwan has implemented their current single window for many years. This papers aims to explore how the cross-border procedures can be facilitated through the systems. Advantages of implementation the single window systems to business supply chains will also be discussed. Finally, some obstacles that might still impact the efficiency of goods clearance procedures which be mentioned.